Rural transformation and differential vulnerability: Exploring adaptation strategies to water scarcity in the Aculeo Lake basin (Chile) - Ocampo-Melgar, Anahi; Barria, Pilar; Chadwick, Cristian; Diaz-Vasconcellos, Raúl (Frontiers in Environmental Science, 2022)
The way of life of agricultural rural territories and their long-term capacity to adapt to changes will be challenged not only by the impacts of climate change; but by increased vulnerability stemming from previous inadequate climate adaptations and development policies. Studies that deepen understanding of the differential causes and implications of vulnerabilities will improve adaptation or transformation of institutions for climate change. The Aculeo basin of Central Chile suffered an extreme 10-years rainfall deficit that resulted in the disappearance of a 12 km2 lake and the economic transformation of the territory. This paper presents a cross-scale exploration of the political, cultural and historical interconnections behind this dramatic story, while critically discussing whether today’s land use configuration reflects the territory’s adaptive capacity. The story is reconstructed using land-use change analysis along with literature review and Causal-Loop Analysis. Results show how previous policies and other human factors contributed to the agroecosystem transformation, creating different vulnerabilities in different economic sectors. Today, what is observed as disparate capacities to adapt to climatic drought is actually the result of historic exacerbations of the vulnerabilities that had significantly contributed to the water scarcity crisis.